2012
DOI: 10.1007/s10526-012-9464-0
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for improving risk communication during the permitting process for entomophagous biological control agents: a review of current systems

Abstract: Paraiso, Oulimathe; Kairo, M.; Leppla, N. C.; Cuda, J. P.; Owens, M.; Olexa, M. T.; and Hight, S. D., "Opportunities for improving risk communication during the permitting process for entomophagous biological control agents: a review of current systems" (2012 Abstract Concerns about potentially irreversible non-target impacts from the importation and release of entomophagous biological control agents (BCAs) have resulted in increasingly stringent national import requirements by National Plant Protection Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This paper is the first case study to evaluate the effects of foods that have experienced growth promotion by plasma irradiation on health. Risk analysis is a process that incorporates risk assessment, risk management, and risk communication 32 , 33 . One of the basic goals of risk assessment is to provide information regarding the basis of a risk management decision.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is the first case study to evaluate the effects of foods that have experienced growth promotion by plasma irradiation on health. Risk analysis is a process that incorporates risk assessment, risk management, and risk communication 32 , 33 . One of the basic goals of risk assessment is to provide information regarding the basis of a risk management decision.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rapid progress in genetic modification of insectpathogenic fungi, both the field efficacy and the ecological risk of a transgenic mycoinsecticide are of public concern (16). A recent study to evaluate the ecological risk of wild-type and engineered Metarhizium strains released into a grassland has revealed that genetic improvement may be acceptable for the fungal agents that lack postrelease gene flow and virulence evolution (17).…”
mentioning
confidence: 99%